(untitled) (Journal of Nepal Geological Society, 2018)
The Belt-and-Road initiative foresees the construction of transportation routes across continents. One of such railway routes is planned from Tibet (China) through the Himalayan Range to Nepal and India, and envisaged to be one of the most important economic corridors. Based on the field investigation, this paper analyses the engineering geological conditions along the proposed route and proposes a preliminary design of the alignment. The alignment starts from Dingri (Tingri) via Jilong from Tibet and ends in Kathmandu, with a total length of 357 km. Based on the geological and geomorphic characteristics, the alignment can be divided into five zones: the mid mountain and wide valley, mid mountain and narrow valley, alluvial fans, tunnel crossing, and, respectively. The railway alignment encounters glaciers, snow and rock avalanches, collapses, landslides, outburst floods and debris flows. There are also many faults, folds and other geological structures together with steep and extensive slopes and long tunnels with a high overburden.